TAJWID LEARNING TRAINING AT TPQ ISLAMIC BOARDING SCHOOL PEWARIS MOSQUE - Zakiya Sifa Amri; Nailatul Muna; Maryono (Institut Agama Islam Syubbanul Wathon Magelang, 2022)
Al-Qur'an is a way of life for every Muslim and, hereafter, obligatory for every Muslim. Recognition and understanding of tajwid are essential to read properly and correctly, especially reading iqra'. However, in Jombong Hamlet, there are still limited assistance and a need for more knowledge about reading law. Therefore, tajwid learning training activities are needed, especially for TPQ children. The mentoring method used is the PAR (Participatory action research) method. Thus, in the process of community service, the team is involved in a participatory manner among parents. After the service, the community became enthusiastic because it added knowledge about reading tajwid properly and correctly with the qiraati method.